Decision Support System for Determining Recipients of Direct Cash Assistance (BLT) Using Simple Additive Weighting in Meunasah Alue Village - Mutia, Rosita; Hasdyna, Novia; Rahmat, Rahmat (Journal of Advanced Computer Knowledge and Algorithms, 2025)
A Decision Support System (DSS) is a computer-based system that generates various decision alternatives to assist management in addressing both structured and unstructured problems using data and models. DSS can also be applied to determine recipients of Direct Cash Assistance (BLT), such as in Meunasah Alue Village. This system is expected to assist the village authorities in selecting BLT recipients more efficiently and effectively each year. The method used in this system is Simple Additive Weighting (SAW), which considers predefined criteria and applies weighted scoring. The aim of this research is to determine suitable BLT recipients in Meunasah Alue Village by using DSS to support accurate and fair decision-making. The results of this study show the top three candidates: Armiati with a score of 227.75, Muliadi with a score of 225.5, and Maimunah with a score of 181.5.